Deconstructing stereotypes: Stature, match-playing time, and performance in elite Women's World Cup soccer - Manning, Ciara N.; Sekiguchi, Yasuki; Benjamin, Courteney L.; Spaulding, McKenna R.; Dierickx, Erin E.; Spaulding, Jayson M.; Davenport, Dayshia M.; Picard-Busky, Jillian R.; Chiampas, George T.; Nassis, George P.; Casa, Douglas J. (Frontiers in Sports and Active Living, 2022)
Recruiting companies recommend elite female soccer players be ≥165 cm (5′5″) in stature. This study investigated if stature limits match-playing time and performance in elite World Cup soccer among players, positions, and countries. We hypothesized stature would not affect match-playing time or performance. Descriptive data were collected on 552 players from 2019 FIFA Women's World Cup. Odds ratios determined likelihood of starting for players <165 cm and ≥165 cm. ANOVAs compared playing time between stature groups, among positions, and between countries. Performance factors including assists, goals, attempts, corners, shots blocked, and defending blocks were reported. Independent t-tests compared differences between players (≥165 cm, < 165 cm). Data are reported, mean difference [95% confidence interval] [MD (95%CI)] and effect sizes (ES). On average, 32.3% of players were <165 cm. Of total players, no differences existed in total minutes (F = 0.98, p = 0.32), matches (F = 0.27 p = 0.59), or average minutes per match (F = 0.48, p = 0.49) between stature groups, regardless of position. No differences existed in playing time between players <165 cm and ≥165 cm among any positions (p > 0.05), or between countries (p > 0.05). Taller mid-fielders exhibited greater performance in goals, assists, attempts, shots blocked, and defending blocks (MD [95%CI] ES; assists, −0.44[−0.76,−0.11]0.59, p = 0.009; goals, −0.35[−0.69,−0.01]0.44, p = 0.047); attempts, 3.14[1.38, 4.90]0.80, p = 0.001; corners, 2.04[0.12, 3.95]0.48, p = 0.037; shots blocked, 0.96[0.40, 1.51]0.75, p = 0.001; defending blocks, 0.43[0.32,0.82]0.48, p = 0.035), however, actual differences were minimal. Our findings indicate stature does not inhibit playing and performing elite women's soccer, as nearly one-third of players were <165 cm.